2013
DOI: 10.1371/journal.pone.0063237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Longitudinal Tracking of Mycobacterium abscessus spp. during Chronic Infection of the Human Lung

Abstract: The Mycobacterium abscessus complex is an emerging cause of chronic pulmonary infection in patients with underlying lung disease. The M. abscessus complex is regarded as an environmental pathogen but its molecular adaptation to the human lung during long-term infection is poorly understood. Here we carried out a longitudinal molecular epidemiological analysis of 178 M. abscessus spp. isolates obtained from 10 cystic fibrosis (CF) and 2 non CF patients over a 13 year period. Multi-locus sequence and molecular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Genetic exchange events affecting the housekeeping genes cya and glpK were observed for the first time by Macheras et al (21,23). We detected probable horizontal gene transfer events affecting the argH, cya, and glpK genes, and Kreutzfeldt et al (38) observed evidence of the same events with the cya, pta, and purH genes, confirming that lateral transfer events of housekeeping genes are somewhat frequent in this group of bacteria.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Genetic exchange events affecting the housekeeping genes cya and glpK were observed for the first time by Macheras et al (21,23). We detected probable horizontal gene transfer events affecting the argH, cya, and glpK genes, and Kreutzfeldt et al (38) observed evidence of the same events with the cya, pta, and purH genes, confirming that lateral transfer events of housekeeping genes are somewhat frequent in this group of bacteria.…”
Section: Resultssupporting
confidence: 81%
“…Interestingly, MLST and wholegenome sequencing approaches helped demonstrate that ST23 is a global strain of M. abscessus subsp. bolletii that causes pulmonary and soft tissue infections, which have been detected in Brazil, the United States, France, Germany, Malaysia, Scotland, Switzerland, and the United Kingdom (17,29,38).…”
Section: Resultsmentioning
confidence: 99%
“…abscessus ST in our series, ST1 (Tables 1 and 2), is the most prevalent isolate in the international MLST database, with isolates recorded from France, Brazil, USA, and Switzerland from both respiratory and soft tissue infection samples [8]. ST26, the second commonest isolate, found in one CF patient at CUH and one at SVUH, has previously been reported from cystic fibrosis patients in Scotland [33], France [8] and England [11]. The other two M. abscessus subsp.…”
Section: Discussionmentioning
confidence: 58%
“…No M. abscessus subsp. bolletii were identified, but these form less than 5% of M. abscessus complex isolates from many countries (Table 3) and their absence could reflect inadequate sampling, as they have been reported from the neighbouring countries of Scotland [33] and England [29].…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have linked the rough colony morphology in MABSC to loss of GPL, increased pathogenicity, and clinical decline in CF patients (10)(11)(12)(13)(14)(15)(16). While most studies of persistent MABSC infection focused on CF patients, less is known about MABSC in the non-CF population regarding presence of mixed populations, clonal relatedness, and phenotypic and genotypic changes of strains collected over time.…”
mentioning
confidence: 99%